2016
DOI: 10.1097/wnf.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Index Estimation of Antiepileptic Drugs: A Systematic Literature Review Approach

Abstract: Objectives To determine whether data obtained from the medical literature can be used to estimate the therapeutic index of 5 antiepileptic drugs (AEDs): carbamazepine, lamotrigine, phenobarbital, phenytoin, and valproate. Methods We performed a literature search using PubMed and Embase to collect published safety, efficacy, and therapeutic monitoring data for 5 AEDs, and extracted all relevant information into a drug- and study-specific drug database. For each AED, we summarized: 1) type, severity, and incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 77 publications
(60 reference statements)
2
50
0
Order By: Relevance
“…This can have serious consequences for narrow therapeutic index (NTID) drugs, where the difference between therapeutic and toxic doses is minimal (e.g. cardenolides, carbamazepine, phenytoin or warfarin [17,18]) and any changes in the concentration of unbound, active form may be poorly tolerated by the organism. A sudden increase in the unbound fraction of the drug may provide a toxic effect [19].…”
Section: Drug-protein Bindingmentioning
confidence: 99%
“…This can have serious consequences for narrow therapeutic index (NTID) drugs, where the difference between therapeutic and toxic doses is minimal (e.g. cardenolides, carbamazepine, phenytoin or warfarin [17,18]) and any changes in the concentration of unbound, active form may be poorly tolerated by the organism. A sudden increase in the unbound fraction of the drug may provide a toxic effect [19].…”
Section: Drug-protein Bindingmentioning
confidence: 99%
“…• Clinical studies show that switching to or among generics has an impact on drug serum levels similar to lots of the same brand • If switching to or among generic AEDs is necessary, physicians should counsel their patients on the need for good adherence to reduce risks on a systematic literature review, only identified phenytoin as an NTI drug; the therapeutic index of phenobarbital and valproate exceeded 2, and available data for carbamazepine and lamotrigine were insufficient for calculations. 6 Regulatory bodies such as the FDA require proof of "bioequivalence" between innovator and generic drugs as the criterion of approving the latter. The FDA criterion for bioequivalence is 90% confidence that the ratios of the test to "reference (innovator)" drug log-transformed mean values for area under the plasma concentration-time curve (AUC) and peak plasma concentration (C max ) lie within an interval of 80%-125% ( Figure 2).…”
Section: Key Pointsmentioning
confidence: 99%
“…Several issues have been raised regarding the use of generic AEDs for patients with epilepsy. Although generally overestimated, a few AEDs may have a narrow therapeutic index (NTI): small fluctuations in drug levels potentially lead to loss of efficacy at the low end or to side effects at the high end of the range . The U.S. Food and Drug Administration (FDA) defines NTI drugs as those having less than a 2‐fold difference between median lethal dose (LD50) and median effective dose (ED50), or less than a 2‐fold difference between minimum blood toxic and effective concentrations, requiring careful titration and monitoring .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations